Evaluasi Usability Aplikasi Tiket.com Menggunakan Metode System Usability Scale (SUS) - Via Alfilaeni; Krisbiantoro, Dwi; Setyaningsih, Gustin (Computer Science Research and Its Development Journal, 2024)
This study focuses on evaluating the usability of the online ticket booking platform, Tiket.com, which despite its popularity, has received numerous negative user reviews. The primary objective of this research was to assess the platform's usability to identify areas of improvement that could enhance user experience. Utilizing the System Usability Scale (SUS) as a quantitative method to process usability data, we conducted an extensive analysis of the platform's interface and interaction features. The SUS provided a framework for assessing user satisfaction and usability efficiency. The results of this study revealed a SUS score of 55.55, which categorizes the usability level of Tiket.com as "OK" according to the Adjective Ranking scale. It falls into the "Acceptable" range, marginally at a Grade D level. These findings suggest that while the platform's usability is generally adequate, there is significant room for improvement. Further analysis indicated that specific enhancements in feature functionality and responsiveness to user feedback are crucial. Enhancing these aspects could substantially improve the overall user experience, ensuring greater user retention and satisfaction. The implications of these findings are significant for future research and practical applications. They suggest that continuous usability evaluations could be instrumental in maintaining and enhancing the effectiveness of online platforms like Tiket.com. This study contributes to the existing literature by providing a detailed usability evaluation of a major online service platform, using a recognized and replicable methodological approach.